Because the value of C equals 13
13+c = -39 c = -39-13 c = -52
13 + c = -9subtract 13 from both sidesc = -9 - 13c = -22
-13 degrees F equals -25 degrees C
c _ = -3 13 just multiply everthing by 13 to get c by itself c _ (13) = -3(13) 13 -3x13=-42 -42 is your answer
13 original united states colonies
You mean: 39=3c 13=c
cards in a suit ( a suit of playing cards, i.e. there are 13 clubs, 13 hearts etc)
Two. One in which C is acute and one where it is obtuse.
13 + 18c = 607 18c = 607 - 13 18c = 594 c = 33
If two sides of a right triangle are 13 and 11, then the third side is either sqrt(290) or 4sqrt(3). (Approx. 17.03 or 6.93)
If 9 - 2c + 3 = -13, then c would be 12.5
a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)
by transitive property
2a. (a, b and c are all equal.)
First, you would add 13+13, which equals 26. Then you would subtract 26-13 which equals 13. So the problem would be 26-13=13.
a - b = c -(a - b) = -c b - a = -c
The answer depends on what R and C are.
C equals the square root of 1000 or 31.622776601683793319988935444327...
Equals C equals is not a correct bond. In order to create a bond, you will need to have an elemental symbon on either side of the equal sign. C equals C would be a correct bond type.
13 times 13 equals 169
It is: 4 times 13 equals 52
a = 20 b = 60 c = 100
The Transitive Property of Equality.
four a = 1 c = 3 a + c = 1 + 3 = 4
Asked By Wiki User
Copyright © 2021 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.